An Exploration of Experiences of English Language Education Students at Almuslim University During Teaching Practice Program (PPL): Expectations, Challenges, And Insights. - Fajarina, Nadiya; Iswadi, Iswadi (Journal of English Education and Social Science, 2024)
This research focused on the interconnected aspects of the experiences which included expectations, challenges, and insights of the English Language Education Department students at Almuslim University. This research provided an in-depth exploration of the perspectives of the students throughout their participation in teaching practice program (PPL). This research employed a qualitative descriptive research method on the English Language Education students from the academic year 2019 at Almuslim university that have participated in PPL for three months starting from September 5th, 2022 to December 5th, 2022. Interview and documentation were the instruments utilized during the research process. The results of the research demonstrated that each PPL participant exhibited significant commonalities in their PPL experiences. Despite their expectations, challenges, and obstacles, the majority of PPL participants indicated that their PPL experiences were highly insightful and beneficial as a foundation of knowledge in the future, facilitating them to evolve into competent, multitalented, qualified, and professional teachers. Kata Kunci: Teaching Practice Program (PPL), Expectations, Challenges, Insights